Uncovering the Novel QTLs and Candidate Genes of Salt Tolerance in Rice with Linkage Mapping, RTM-GWAS, and RNA-seq - Weilong Kong (SpringerOpen, 2021)
Abstract Salinity is a major abiotic stress that limits plant growth and crop productivity. Indica rice and japonica rice show significant differences in tolerance to abiotic stress, and it is considered a feasible method to breed progeny with stronger tolerance to abiotic stress by crossing indica and japonica rice. We herein developed a high-generation recombinant inbred lines (RILs) from Luohui 9 (indica) X RPY geng (japonica). Based on the high-density bin map of this RILs population, salt tolerance QTLs controlling final survival rates were analyzed by linkage mapping and RTM-GWAS methods. A total of seven QTLs were identified on chromosome 3, 4, 5, 6, and 8. qST-3.1, qST-5.1, qST-6.1, and qST-6.2 were novel salt tolerance QTLs in this study and their function were functionally verified by comparative analysis of parental genotype RILs. The gene aggregation result of these four new QTLs emphasized that the combination of the four QTL synergistic genotypes can significantly improve the salt stress tolerance of rice. By comparing the transcriptomes of the root tissues of the parents’ seedlings, at 3 days and 7 days after salt treatment, we then achieved fine mapping of QTLs based on differentially expressed genes (DEGs) identification and DEGs annotations, namely, LOC_Os06g01250 in qST-6.1, LOC_Os06g37300 in qST-6.2, LOC_Os05g14880 in qST-5.1. The homologous genes of these candidate genes were involved in abiotic stress tolerance in different plants. These results indicated that LOC_Os05g14880, LOC_Os06g01250, and LOC_Os06g37300 were the candidate genes of qST-5.1, qST-6.1, and qST-6.2. Our finding provided novel salt tolerance-related QTLs, candidate genes, and several RILs with better tolerance, which will facilitate breeding for improved salt tolerance of rice varieties and promote the exploration tolerance mechanisms of rice salt stress.